Understanding the Self in Individuals with Autism Spectrum Disorders (ASD): A Review of Literature - Huang, Ann X.; Hughes, Tammy L.; Sutton, Lawrence R.; Lawrence, Marissa; Chen, Xiaohan; Ji, Zhe; Zeleke, Waganesh (Frontiers in Psychology, 2017)
When the system of self is explored in individuals with Autism Spectrum Disorders (ASDs), it is important to measure it via both their own perceptions of the self and their understanding of others’ perceptions on themselves at a multidimensional level. This paper reviews existing research in this area using a three-dimension approach. Researchers have found that impairments in the self-system are usually correlated with these individuals’ social and cognitive functioning levels: high functioning individuals with ASD who have higher IQ are found to have better awareness of their limitations in social and communication domains than those with lower IQ. Many researchers believe that there are impairments in the psychological (but not physical) self in individuals with ASD, such as theory of mind deficits due to social and communicative impairments. On the other hand, some researchers argue that individuals with ASD have selective rather than global impairments in the self. In other words, the impairment usually lies in a specific aspect of functioning in individuals with ASD. Insights from the review of existing literature on this topic may be able to shed some lights on the development of effective intervention programs to improve social communication deficits in this population.